GENRE, FRAGMENTATION AND MONTAGE IN THE BRAZILIAN NOVEL: ZERO, BY IGNÁCIO DE LOYOLA BRANDÃO - Vertuan, Éderson (WEB REVISTA LINGUAGEM, EDUCAÇÃO E MEMÓRIA, 2018)
The purpose of this proposed investigation is to explain what the book Zero tries to express and how it does so. It is hypothesized that the mixture of genres through the use of the process of montage, in the particular case of Zero, creates a metaphor for the turbulence of the military period and establishes the novel genre as a metaphor for an abusive dictatorial regime.